The kinetics of the pineapple juice fermentation process: a physicochemical approach - Souza, Bárbara Caroline Nunes de; Sabino, Lia Lucia; Silva, Matheus Felipe de Oliveira; Castilhos, Maurício Bonatto Machado de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
The chemical composition of fermented beverages is determinant to delineate their sensory characteristics since they are dependent on the fruit cultivation, processing, stabilization, storage, and the intrinsic characteristics of the producing region. Alcoholic fermentation is a biochemical process of relevance for the production of beverages with unique chemical and sensory features and the analysis of the fermentative behavior promotes real conditions to control this process to maximize the quality of the produced beverage. The present project aimed at studying the fermentation kinetics of the Pearl and Hawaiian pineapple juices, commercialized in the city of Frutal/MG, determining its physical-chemical properties to observe the necessary parameters to optimize the control of the fermentative process. The beverages showed high acidity (maximum 41.7 g/L in citric acid) and dry extract (47.7 g/L after fermentation), resulting in full-bodied beverages. All beverages were classified as dry (reducing sugar content below 4 g/L), the maximum alcohol content of 7.93 % v/v (Pearl) and 5.10 % v/v (Hawaiian), and with high total phenolic content (maximum of 1049 mg/L for Pearl and 852 mg/L for Hawaiian) assuming high antioxidant capacity. The kinetic parameters obtained showed that 72 hours after the start of alcoholic fermentation can be considered as a cutoff time for the consolidation of the fermentative process.